Key issues for BAPA+40: South-South cooperation and the BAPA+40 subthemes - Vicente Paolo B. Yu (South Centre, 2019)
Developing countries today face multiple interlinked macroeconomic, financial, climate, and development challenges. South-South cooperation is an important element for developing countries to meet these challenges individually and collectively, and in multilateral North-South dialogue and global governance. The overall theme of the Second High-level United Nations Conference on South-South Cooperation (40 years after the Buenos Aires Plan of Action for Promotion and Implementing Technical Cooperation among Developing Countries/BAPA+40) is the "Role of South-South cooperation and the implementation of the 2030 Agenda for Sustainable Development: challenges and opportunities", with sub-themes. This research paper will present some concepts relating to South-South cooperation that have been developed by the South and the United Nations system, and looks at some issues that would be relevant to discussions that may be undertaken with respect to Subthemes (i) "Comparative advantages and opportunities of South-South cooperation"; (ii) "Challenges and the strengthening of the institutional framework of South-South cooperation and triangular cooperation"; and (iv) "Scaling up the means of implementation of the 2030 Agenda for Sustainable Development in support of South-South cooperation and triangular cooperation". It concludes by providing recommendations for the consideration of developing countries in response to the various subthemes, as inputs to support the active engagement by developing countries in the negotiations for the BAPA+40 outcome document.
Keywords: 300; Internationale Wirtschaftsbeziehungen; Komparativer Vorteil; Süd-Süd-Beziehungen; Nachhaltige Entwicklung; Welt